Exploring the Association Between Military Base Neighborhood Characteristics and Soldiers' and Airmen's Outcomes - Meadows, Sarah O. (RAND Corporation, 2013)
This report explores the applicability of neighborhood theory and social indicators research to understanding the quality of life in and around military bases. It also highlights gaps in neighborhood study methodology that need to be addressed in future research. Finally, it outlines how a more in-depth neighborhood analysis of military installations could be conducted.